Resilience and Coping Strategies during COVID-19: Perspectives from Agricultural Enterprise Farmers - Chumpanya, Jiraporn; Panpakdee, Chaiteera (Journal of Ecohumanism, 2025)
COVID-19 posed threats to Thailand, particularly affecting agricultural enterprises. This study examines coping strategies of the Khok Sawang Agricultural Enterprise (KSAE) in Khon Kaen province in response to disturbances of the COVID-19 pandemic. A purposive sample of 75 members from the KSAE was analyzed using a mixed-methods approach. Data were collected through semi-structured questionnaires and in-depth interviews. Quantitative data were computed using SPSS, qualitative insights were derived through thematic analysis. The findings indicate that respondents faced considerable challenges across four domains: production and trade, food security, health, and income. Specifically, 86.7% reported income losses, 82.7% indicated increased mental health stress, and 70% reported reduced access to healthcare services. Market pressures, rising production costs, and decreased consumer demand collectively resulted in a 30% decline in production. To cope with these disruptions, respondents adopted diverse coping strategies. In terms of production, farmers reduced working hours, implemented daily wage cuts, and adopted digital platforms to facilitate direct sales. Health-related strategies included engagement in vaccination schemes and enhancing social networks to provide emotional support. This study underscores the resilience in navigating the extensive disturbances of COVID-19. It emphasizes the need for integrated policy frameworks that enhance farmers’ resilience to deal with future crises.